2007
DOI: 10.1177/112067210701700607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Complications, and Incidence of Intraoperative Floppy Iris Syndrome in Patients Taking Tamsulosin

Abstract: IFIS occurred in 1.6% of cases having phacoemulsification. Intracameral adrenaline usage did not change the IFIS occurrence rate, but it seemed to be effective in preventing intraoperative miosis. There are still many questions about IFIS, and there is need for future studies strengthening the understanding of IFIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 16 publications
3
39
0
5
Order By: Relevance
“…3,5 Previous studies have reported an association between IFIS and intake of α-blockers, which are commonly used for the treatment of benign prostatic hyperplasia. Specifically, IFIS was independently associated with tamsulosin, 1,6-10 doxazosin, 2,9,11 terazosin, 12 alfuzosin, 8,10,13 silodosin, 14 or labetalol, a selective α-and β-blocker. 15 Interestingly, a meta-analysis of the risk factors for IFIS demonstrated a hierarchy in the magnitude of the associations between the various α-blockers and IFIS.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Previous studies have reported an association between IFIS and intake of α-blockers, which are commonly used for the treatment of benign prostatic hyperplasia. Specifically, IFIS was independently associated with tamsulosin, 1,6-10 doxazosin, 2,9,11 terazosin, 12 alfuzosin, 8,10,13 silodosin, 14 or labetalol, a selective α-and β-blocker. 15 Interestingly, a meta-analysis of the risk factors for IFIS demonstrated a hierarchy in the magnitude of the associations between the various α-blockers and IFIS.…”
Section: Introductionmentioning
confidence: 99%
“…Masket & Belani injected 0.3 -0.5 mL epinephrine diluted with BSS (1 : 2500) intracameral and placed under the iris with excellent results (Masket & Belani 2007). Takmaz & Can suggested a mixture of 0.1 mL non-preserved epinephrine (0.5 mg /mL) diluted with 2 mL BSS (1 : 4000 solution) (Takmaz & Can 2007). They reported no change in the incidence of IFIS, but the mixture seemed effective in order to prevent miosis.…”
Section: Intracameral Injection Of Epinephrinementioning
confidence: 99%
“…Furthermore, IFIS developed in 40% to 100% of patients exposed to tamsulosin and 0% to 66.7% of patients exposed to other alpha-blockers. [5][6][7][8][9][10][11][12][13][14] In a retrospective review of 1612 cataract surgeries performed in 1298 patients, Srinivasan and colleagues found that 65 patients (5%) were on an alphablocker for LUTS/BPH. IFIS occurred in 14.7% of these 65 patients (14/95 surgeries).…”
Section: Ifismentioning
confidence: 99%
“…However, some authors, including ourselves, have shown that having IFIS in one eye does not necessarily result in IFIS in the second eye. 11,15,16 Bell and colleagues assessed the risk of adverse events following cataract surgery. They found that exposure to tamsulosin within 14 days of surgery was significantly associated with serious postoperative ophthalmologic adverse events.…”
Section: Is the Effect Of Alpha-blockers On The Iris Permanent?mentioning
confidence: 99%